2011
DOI: 10.5487/tr.2011.27.4.231
|View full text |Cite
|
Sign up to set email alerts
|

Thirteen-Week Oral Dose Toxicity Study of G. bimaculatus in Sprague-Dawley Rats

Abstract: Gryllus bimaculatus (Gb) was orally administered at doses of 0, 0.04, 0.2, 1 and 5 g/kg bw/day for 13 consecutive weeks. There were no observed clinical signs or deaths related to treatment in all the groups tested. Therefore, the approximate lethal oral dose of G. bimaculatus was considered to be higher than 5 g/kg in rats. Throughout the administration period, no significant changes in diet consumption, ophthalmologic findings, organ weight, clinical pathology (hematology, clinical chemistry, coagulation, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Specifically, the cricket G. bimaculatus has traditionally been consumed in different parts of the world including northeast Thailand, which recorded 20,000 insect farmers in 2011 40 . Studies have reported no evidence for toxicological effects related to oral consumption of G. bimaculatus by humans 41 , 42 , neither were genotoxic effects detected using three different mutagenicity tests 43 . A rare but known health risk associated with cricket consumption, however, is sensitivity and allergy to crickets 44 , 45 .…”
Section: Discussionmentioning
confidence: 97%
“…Specifically, the cricket G. bimaculatus has traditionally been consumed in different parts of the world including northeast Thailand, which recorded 20,000 insect farmers in 2011 40 . Studies have reported no evidence for toxicological effects related to oral consumption of G. bimaculatus by humans 41 , 42 , neither were genotoxic effects detected using three different mutagenicity tests 43 . A rare but known health risk associated with cricket consumption, however, is sensitivity and allergy to crickets 44 , 45 .…”
Section: Discussionmentioning
confidence: 97%
“…bimaculatus has traditionally been consumed in different parts of the world including northeast Thailand, which recorded 20,000 insect farmers in 2011 40 . Studies have reported no evidence for toxicological effects related to oral consumption of G. bimaculatus by humans 41,42 , neither were genotoxic effects detected using three different mutagenicity tests 43 . A rare but known health risk associated with cricket consumption, however, is sensitivity and allergy to crickets 44,45 .…”
Section: The Importance Of Cricket Genomesmentioning
confidence: 98%
“…including rearing for consumption, issues relevant to its biochemical composition (Ghosh et al, 2017), human health and safety (Ahn et al, 2011;Ryu et al, 2016), putative health benefits (Ahn et al, 2014;Dong-Hwan et al, 2004;Hwang et al, 2019;Park et al, 2019), and processing techniques (Dobermann, Field, & Michaelson, 2019) have been extensively described. Thus, the genome of G. bimaculatus herein described, adds to this body of biological knowledge by providing invaluable information that will be required to maximize the potential of this cricket to become an increasingly significant part of the worldwide diet in the future.…”
Section: The Importance Of Cricket Genomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Grasshoppers that are roasted can also be a food source, but these are not typically consumed in Korea. The observed adverse effect level (NOAEL) of Gb is reportedly higher than 5 g/kg body weight/day, as shown in a 13-week oral dose toxicity study in Sprague-Dawley rats (4) .…”
Section: Introductionmentioning
confidence: 96%